P145 Ultrasonographic parameters associated with mucosal healing 1 year after infliximab therapy in Crohn's Disease: a multicentric and prospective study. (21st January 2022) - Nascimento, C; Frias Gomes, C; Morão, B; Cúrdia Gonçalves, T; Dias de Castro, F; Moreira, M J; Cotter, J; Pereira, F; Caldeira, A; Rosa, C; Macedo, G; Macedo, C; et al.
Abstract: Background: Bowel wall thickness (BWT) is an accurate ultrasonographic parameter to assess disease activity in Crohn's disease (CD). The IBUS-SAS score includes BWT, doppler sign, loss of stratification and inflammatory fat (i-fat) and allows a reproducible assessment of inflammation in CD using intestinal ultrasound (IUS). Our aim: to assess clinical, laboratorial and ultrasonographic predictors of mucosal healing (MH) at 1 year of infliximab (IFX) therapy. Methods: Prospective multicentric cohort study including patients with active CD starting IFX. Harvey-Bradshaw index, C-reactive protein (CRP), fecal calprotectin (FC) and IUS were performed at week 0, 14, 30 and 54. IUS remission was defined as BWT normalization (≤3mm) in the most affected segment. Ileocolonoscopy was performed at W0 and W54. MH was defined as SES-CD <3 with no ulcers. Results: We included 28 patients with CD (61% male; mean age of 34±12y). Clinical, laboratory and sonographic parameters are shown in Table 1. At week 54, 89% were in clinical remission, 79% had normalization of CRP and FC, 50% had IUS remission and 39% had MH. MH at W54 was associated with lower BWT at W14 (3.7 vs 5.2mm, p=0.049), lower Limberg score at W14 (1 vs 2, p=0.006), lower levels of i-fat at W14 (18 vs 72%, p=0.006) and lower IBUS-SAS score at W0, W14 and W30 (47 vs 71, p=0.002; 26 vs 58, p=0.001; 25 vs 50 p=0.046). We found a fair to good correlation between SES-CD W54 and BWT at W14 (r=0.45, p=0.015), Limberg score at W14 (r=0.4, p=0.037), IBUS-SAS at W0 and W14 (r=0.49, p=0.008; r=0.58, p=0.001). The area under the curve of IBUS-SAS for MH was 0.86 at W0 and W14 and 0.69 at W30. Best IBUS-SAS cut-off value was 27.6 at W14. Conclusion: Lower values of BWT, Limberg score and i-fat after induction (W14) were associated with MH at 1 year of therapy. IBUS-SAS score at W14 had the highest AUC to predict MH at 1 year. Early IUS monitoring can be a helpful tool to predict response to therapy in CD patients at 1 year.